2021
DOI: 10.1093/alcalc/agab019
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Risky Drinking During the COVID-19 Pandemic Assessed via Longitudinal Cohort Design: Associations With Racial Tensions, Financial Distress, Psychological Distress and Virus-Related Fears

Abstract: Background The COVID-19 pandemic has created disruptions to daily life resulting in wide-spread unemployment and psychological distress. Recent studies have reported high rates of alcohol use during this time; however, longitudinal data remain scarce and factors associated with increases in high-risk drinking observed over time are unknown. Aims The current study examined changes in high-risk drinking patterns across four 7-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…We should note that the discrimination item did not specifically refer to Black Americans or Asian American/Pacific Islanders, who were the most likely to experience discrimination during the pandemic ( Chen et al, 2020 ; Ruiz et al, 2020 ; C. Wu et al, 2021 ). We also did not find evidence to suggest that COVID-19 concern was associated with alcohol use net the effects of other stressors, which differs from findings that show virus-related fears were linked to lower rates of risky drinking ( Lechner et al, 2021 ). While COVID-19 concern has been linked to substance use in other studies ( Rogers et al, 2020 ), we only found that it was associated with marijuana use over the past 30 days.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We should note that the discrimination item did not specifically refer to Black Americans or Asian American/Pacific Islanders, who were the most likely to experience discrimination during the pandemic ( Chen et al, 2020 ; Ruiz et al, 2020 ; C. Wu et al, 2021 ). We also did not find evidence to suggest that COVID-19 concern was associated with alcohol use net the effects of other stressors, which differs from findings that show virus-related fears were linked to lower rates of risky drinking ( Lechner et al, 2021 ). While COVID-19 concern has been linked to substance use in other studies ( Rogers et al, 2020 ), we only found that it was associated with marijuana use over the past 30 days.…”
Section: Discussioncontrasting
confidence: 99%
“…In the COVID-19 pandemic, reports have been mixed, with some studies showing elevated rates of substance use in the general adult population ( Czeisler et al, 2020 )( Pollard et al, 2020 ). Prior studies have identified key stressors resulting from the pandemic, such as psychological distress, financial worries, racial tensions, personal or familial difficulties, social isolation and lack of social support ( Capasso et al, 2021 ; Currie, 2021 ; Lechner et al, 2021 ; MacMillan et al, 2021 ; Rolland et al, 2020 ). Studies have suggested that people may have used substances to cope with these COVID-19 stressors ( Czeisler et al, 2020 ) and the mental health symptoms resulting from the stressors ( Firkey et al, 2020 ; Horigian et al, 2020 ; Jones et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have included cross-sectional panel or longitudinal methodology. Some of these key studies involved localized data (e.g., Bade et al, 2021 ; Charles et al, 2021 ; Evans et al, 2021 ; Fruehwirth et al, 2021 ; Graupensperger et al, 2021 ; Jackson et al, 2021 ; Lechner et al, 2021 ; Minhas et al, 2021 ; Ryerson et al, 2021 ; Salazar-Fernández et al, 2021 ; Ward et al, 2021 ), while others utilized national data. Of those using national data, some have included trend data ( Schulenberg et al, 2021 ) but have not specifically examined changes during the pandemic while controlling for existing trends; others have included limited data points (i.e., one or two) preceding the COVID-19 pandemic (e.g., Barbosa et al, 2021 ; Daly and Robinson, 2021 ; Oksanen et al, 2021 ; Pollard et al, 2020 ), while others included only data points after pandemic onset (e.g., Irizar et al, 2021 ; Nordeck et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mental health of students can play a significant role in handling the psychological issues related to COVID-19 and financial status, and for better academic performances ( Kokkinos et al, 2022 ). Care should be taken that the stress related to COVID and threats to financial wellbeing can increase the chances for negative addictions including alcohol ( Lechner et al, 2021 ; Rodriguez et al, 2021 ). The psychological linkages of the risk in financial wellbeing during COVID can have significant impacts on the children.…”
Section: Introductionmentioning
confidence: 99%